The Effects of eGovernment Efficiency on Subjective Wellbeing - Fan, Mingyue; Epadile, Motswedi; Qalati, Sikandar Ali; Qureshi, Naveed Akhtar (Frontiers in Psychology, 2022)
Undoubtedly, the internet has become the most convenient and efficient communication and service delivery channel adopted by most government agencies, referred to as eGovernment. This study explores how eGovernment efficiency influences users’ subjective wellbeing (SWB), using trust as a covert stimulus with the capacity to alter individuals’ overt behavior (utilization). Covert and overt stimuli act as significant factors influencing the relationship between citizens and the online environment, moderated by socio-demographic characteristics. Using situation–organism–behavior–consequence theory, we propose a research model consisting of online environment eGovernment efficiency (the situation) influencing trust development (the organism), which in turn influences utilization (the behavior), generating an impact on an individuals’ SWB (the consequence). We followed the structural equation modeling (SEM) approach to analyze the data survey N = 300, using Amos statistical techniques. Results reveal that the correlation between eGovernment efficiency and trust is positive and strong, trust and utilization is positive and moderate, and the correlation between utilization and SWB is positive and very strong. Stepwise regression analysis reveals that the control variables affect the relationship between eGovernment efficiency and trust. In the regression model: the highest education level explained 36% of the variance (model 1); adding age increased the variance explained to 39% (in model 2), and adding internet use frequency increased the variance explained to 41% (model 3). This study develops theoretical concepts of eGovernment use and how it affects citizens by indicating the psychological and behavioral situations as antecedents and mediators influencing SWB. It also provides practical suggestions for improving systems to correlate users’ feelings and behavior patterns to motivate trusting behavior, positively impacting users’ SWB to benefit citizens effectively.